2019
DOI: 10.1039/c9nj00526a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,3-bis-organochalcogenyl-benzo[b]chalcogenophenes promoted by Oxone®

Abstract: We report here an alternative and tunable metal-free synthesis of benzo[b]chalcogenophenes via the electrophilic cyclization of 2-functionalized chalcogenoalkynes promoted by Oxone®.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 117 publications
1
39
0
Order By: Relevance
“…Thus, based on the above observations and on previous reports involving electrophilic cyclization reactions, [70][71][72] the reactivity of Oxone ® [40,43,81] and reactions under ultrasonic irradiation, [77][78][79][80][81] a plausible mechanism for the formation of chalcogenophenes 7-9 from 1-3 is presented in Scheme 4.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…Thus, based on the above observations and on previous reports involving electrophilic cyclization reactions, [70][71][72] the reactivity of Oxone ® [40,43,81] and reactions under ultrasonic irradiation, [77][78][79][80][81] a plausible mechanism for the formation of chalcogenophenes 7-9 from 1-3 is presented in Scheme 4.…”
Section: Resultsmentioning
confidence: 57%
“…Based on our previous studies using Oxone ® in reactions to prepare selenium-containing pyrazoles [40] and chalcogenophenes, [43] we started our studies by reacting (Z)-butyl(1,4-diphenylbut-1-en-3-yn-1-yl)selane 1 a (0.250 mmol) with diphenyl diselenide 4 a (0.125 mmol) in the presence of Oxone ® (0.250 mmol) and ethanol as the solvent (2.0 mL). The mixture was stirred at room temperature for 24 h, and no reaction was observed, with the starting materials being recovered almost quantitatively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lewis acid (FeCl 3 ) mediated generation of selenium electrophile has been used for preparation of 3‐selanyl benzo[ b ]furans and indoles as well. Very recently, Perin et al reported the synthesis of 2,3‐dichalcogenyl‐substituted benzo[ b ]chalcogenophenes employing oxone induced generation of selenium electrophile . Another sulfur‐containing oxidant (persulfates) induced generation of selenium electrophile has been used for the direct selenylation of indole and arenofurans .…”
Section: Introductionmentioning
confidence: 99%